1994
DOI: 10.1002/mpo.2950230602
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated nonlymphoblastic lymphoma of childhood: A childrens cancer group study, CCG‐552

Abstract: Advanced stage SNCCL requires better CNS-directed chemotherapy to reduce the CNS failure rate; however, the achievement of durable disease-free survival in four of 11 patients with CNS disease without use of cranial irradiation suggests merit for further evaluation of chemotherapy-only strategies. DLCL patients do not need intensive CNS-directed chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…Prospective studies conducted in Europe and the United States in the late 1980s demonstrated the importance of agents such as HD-MTX, cyclophosphamide or ifosfamide, and high-dose cytarabine in the management of this malignancy. [1][2][3][4][5][6][7][8][9][15][16][17][18] These studies also contributed to the identification of additional risk factors, such as tumor burden, resection status, and serum LDH levels, that, along with disease stage, had an impact on prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective studies conducted in Europe and the United States in the late 1980s demonstrated the importance of agents such as HD-MTX, cyclophosphamide or ifosfamide, and high-dose cytarabine in the management of this malignancy. [1][2][3][4][5][6][7][8][9][15][16][17][18] These studies also contributed to the identification of additional risk factors, such as tumor burden, resection status, and serum LDH levels, that, along with disease stage, had an impact on prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies conducted within the Children's Cancer Group (CCG) by Anderson et al 1,2 demonstrated that the 4-drug regimen COMP (cyclophosphamide, vincristine, methotrexate, and prednisone) was significantly more effective than the 10-drug regimen LSA2-L2 (cyclosphosphamide, vincristine, methotrexate, daunorubicin cerubidine, prednisone, cytarabine, thioguanine, asparaginase, hydroxyurea, and carmustine). Subsequently, the CCG demonstrated the efficacy of the CHOP regimen in obtaining high complete response (CR) rates 3 and improved on this strategy with the development of the 'Orange' regimen, 4 while pediatric hematology and oncology groups in Europe were also gradually achieving improved results using short, high-dose intensity regimens. In particular, the French Society of Pediatric Oncology (SFOP) designed a series of consecutive protocols, LMB84, 5 LMB86, 6 and LMB89, 7 that yielded EFS rates Ͼ 85% even in groups with poor prognosis (i.e., groups in which patients with a high percentage of blasts in bone marrow and patients with central nervous system [CNS] involvement were included).…”
mentioning
confidence: 99%
“…Finlay et al 4 treated 68 children with advanced non-lymphoblastic lymphoma with a three-cycle induction lasting 9 weeks (cyclophosphamide, adriamycin, vincristine, prednisone) (intensive CHOP), intensive consolidation and intrathecal triple chemotherapy, and five 9-week courses of maintenance therapy. The intensive CHOP induction utilized in that study resulted in a 97% complete response rate (CR).…”
Section: Demonstrated That the Addition Of Daunomycin To Comp (D-compmentioning
confidence: 99%
“…The intensive CHOP induction utilized in that study resulted in a 97% complete response rate (CR). 4 Results of CCG-8605, a retrieval protocol designed for children with recurrent solid tumors and/or lymphomas, demonstrated that the combination of ifosfamide and etoposide was an active combination in the reinduction therapy of recurrent/refractory non-Hodgkin's lymphoma (NHL) (J Miser, CCG-8605 Final Report, November 1997). Children with recurrent large cell lymphoma treated on this retrieval regimen had 20% and 40% CR and PR rates, respectively.…”
Section: Demonstrated That the Addition Of Daunomycin To Comp (D-compmentioning
confidence: 99%
“…15,[42][43][44][45][46] CNS or bone marrow involvement, as reported previously by us and by other groups, does not seem to affect the rate of response, because patients with Stage III disease and Stage IV disease fared the same. According to our experience and that of other groups, [47][48][49][50][51][52][53] CNS prophylaxis beyond the induction period may be indicated, but only in patients who are at high risk for local CNS invasion, like those with head and neck disease.…”
Section: Discussionmentioning
confidence: 99%